Identifying the dimensions of gender justice in the Iranian Ministry of Sport and Youth - Javad Bani Hassan; Zahrasadat Mirzazadeh; Mahdi Talebpour; Ahamadreza Asgharpourmasouleh (Universidad de Murcia, 2023)
In modern times, sports have attracted the attention of different societies. Social, economic and political functions are one of the reasons. In Iran, the role of the Ministry of Sports and Youth is very important in managing sports in the country. Justice has been supposedly one of the pillars of ethical management in organizations, along with performance improvement. One example of justice in organizations is gender justice. The aim of this study was to provide valuable information to sports activists in the country by identifying the dimensions of gender justice in the Ministry of Sports and Youth and identify ways to expand gender justice according to employees' perceptions. The current research is practical in terms of purpose and qualitative in terms of method, employing a thematic analysis strategy. The sample consisted of 7 management experts and sociologists who had studied, researched, or gained experience in the field of the present study (gender justice in organizations). The researchers used a semi-structured interview, which is suitable for qualitative research in terms of flexibility and depth. The "Inter Coder Reliability (ICR)" method was used to measure the reliability of the interviews conducted. The data were coded using MAXQDA2018 software. The results showed that perceptions of gender justice include 3 main themes (distributive justice, procedural justice and interactional justice) and 19 sub-themes. The expansion of gender justice in the Ministry of Sports and Youth, as the country's sports policy organization, can seemingly be effective in improving performance. It also has positive social and cultural effects on all sports areas of the country.